Análise do processo de logística reversa em empresas de telecomunicações - Tonini, Magrid Blanco (2015)
In the recent years, the reverse logistics has acquired a significant importance in the companies, both in the international and national context. Due to this growth, this paper presents an overview of the reverse logistics, its use, its advantages, as well as, some existing practices, and the gain of the companies in reducing costs through the use of the reverse logistics, through the reuse of the discarded material. Focused on the applicability of the reverse logistic, this research project aims to analyze the reverse logistics models into different segments through the existing theoretical framework, and compare them through the sources of evidence, to the case studies in Alfa and Beta companies operating in the telecommunications area. The Reverse logistics is a technology that operates in several areas, contributing to the strategic management of the companies, causing economic gains and thus providing competitive advantage to the companies that join it. For this study, the researcher used as instruments of work, a qualitative exploratory approach to case study with cross sectional perspective. As the technical procedures, the method multiple case study were used. The data collection was through primary data, which was held semi-structured interviews with existing managers and employees of the companies Alfa and Beta Telecommunications aimed to identify the reverse logistics practices, and the secondary data obtained from the literature and document analysis (available documents). The data indicate some actions in the field of the reverse logistics that Alfa and Beta companies perform in a descriptive way about what benefits, difficulties, processes and / or areas used in day-to-day, also showing the operating cycle companies do to make the collection of equipment and profit in the activities. Data analysis showed that reverse logistics is present in the strategic area of both companies from the reduction in the purchase of new equipment by recovering the Telecommunications equipment already used and the security of information when performed the reverse flow. This study made it possible to note justifications and indications of improvement in existing processes in the companies studied. It was noticed that one of the biggest gains was from the correct disposal causing fostering in environmental sustainability